Infrared Radiation of Graphene Electrothermal Film Triggered Alpha and Theta Brainwaves. Issue 12 (9th November 2022) - Lu, Yanghua; Yang, Renyu; Dai, Yue; Yuan, Deyi; Yu, Xutao; Liu, Chang; Feng, Lixuan; Shen, Runjiang; Wang, Can; Dai, Shenyi; Ge, Qi; Lin, Shisheng
Abstract : The alpha and theta frequency brainwave activity in electroencephalogram (EEG) signal is proven to correlate with attention, inhibitory processes, memory, perceptual abilities, and sleep. The decreasing of brainwaves is demonstrated to be the reason of aging and even Alzheimer's disease, so triggering alpha and theta brainwave activity may bring positive behavioral modifications such as promoting health care and a quick sleep. Herein, it is discovered that infrared radiation from multilayer graphene electrothermal film can obviously promote the appearance of alpha and theta brainwaves in the human brain. In particular, the occurrence frequency and duration time of the alpha and theta waves in EEG can be effectively enhanced up to 2.3/2.9 and 3.0/4.1 times, respectively. The comparative effect of different working temperatures and heating materials is systematically investigated, indicating efficient infrared radiation from the multilayer graphene electrothermal film, which coincides with the human‐body thermal‐radiation wavelength range from 7 to 14 μm, may be the main mechanism for this enhancement. The multilayer graphene film electrical heater represents a convenient and surprising way for triggering alpha and theta brainwaves, which has many potential applications in the area of enlarged healthcare requirements. Abstract : A multilayer graphene electrothermal film is proposed to trigger enhanced alpha and theta brainwaves in the human brain, attributing to the efficient infrared radiation from graphene located in the range from 7 to 14 μm. This work represents a convenient and noninvasive characterization tool for enhancing the activity of brain waves, which has many potential applications in the area of enlarged healthcare requirements.